ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON PATIENT LOYALTY AT BUNDA LIWA MOTHER AND CHILD HOSPITAL IN WEST LAMPUNG - Paramartha, Vip; Rulia , Rulia; Pratama Duarsa, Habibi Adhi (Transpublika Publisher, 2024)
Patient loyalty is an important factor that hospitals need to remain able to survive amidst increasingly fierce competition. For this reason, it is important to analyze the factors that influence patient loyalty, one of which is service quality. This research aims to evaluate the influence of various factors such as tangibility, responsiveness, assurance, empathy, and reliability on patient loyalty, exploring both their individual and combined effects. The theoretical framework guiding this study is based on principles of hospital management. Using a descriptive and verification analysis approach, quantitative data was collected through questionnaires distributed to 72 participants, selected through accidental sampling. Data analysis employed multiple linear regression analysis conducted with SPSS 26 software. The results of the descriptive analysis revealed that TERRA at RSIA Bunda Liwa West Lampung was rated as good to excellent, with average scores for Tangible (4.35), Empathy (4.25), Responsiveness (4.28), Reliability (4.28), and Assurance (4.45). Patient Loyalty (4.30). The verification analysis demonstrated a significant and positive correlation between tangibility, empathy, responsiveness, reliability, assurance and patient loyalty when considered individually. Moreover, when considered collectively, these factors were found to collectively exert a positive and significant impact on patient loyalty.